Pengaruh Pemberian Jus Melon SGH Tefa Polije Kombinasi Jeruk Nipis Terhadap Hipertensi Sebagai Upaya Penurunan PTM - Puspita, Surya Dewi; Ratri, Putri Rahayu; Jannah, Miftahul; Fitriyah, Dina; Yuanta, Yohan; Kartika, Ria Chandra (ARTERI : Jurnal Ilmu Kesehatan, 2024)
The prevalence of hypertension among people aged ≥18 years is 34.1%, with a prevalence of 36.9% in women and 31.3% in men. East Java Province ranks sixth with a hypertension prevalence of 36.32%, while the number of hypertension patients in Jember Regency, according to data from the Jember Health Office in 2023, is 198,562 people, and the number of hypertension patients at the Jenggawah Health Center is 6,461 people. The aim of the study is to determine the effect of giving SGH Tefa Polije Melon Juice combined with Lime on Hypertension. The research method used is a Quasi-Experiment with a Pretest Posttest Non-Equivalent Control Group approach with a sample size of 30 people, and the variable in this study is blood pressure. The results of data testing with the Mann Whitney test between the systolic and diastolic blood pressure of the control group and the treatment group showed p-values of 0,621 and 0,952 (p>0,005), indicating no significant difference in systolic and diastolic blood pressure between the groups before the intervention. This shows that the study can proceed to the stage of giving the treatment with melon juice combined with lime. There was a difference in the average blood pressure between the control group and the treatment group after the intervention in systolic pressure (p=0,004) and diastolic pressure (p=0,001). Systolic (p=0,003) and diastolic (p=0,002) pressures in the treatment group showed significant differences before and after the intervention. Based on these results, it can be concluded that there is an effect of giving melon juice combined with lime on hypertension, and there is no significant difference in systolic and diastolic blood pressure between the groups before the intervention. For future research, it is expected to measure the respondents' dietary intake parameters.